Emergence of procedure - law in India and its social and political background - Chaturvedi, D.P. (2010)
In this paper I have tried my best to discover the emergence of Procedural Law in India. In Ancient India, available literature displays a stage of development where state was not in existence. Social traditions controlled the community. There are sufficient indications that show that state came in existence to remove social anarchy. Actually, the affectivity of any legal process depends over the degree of development of its sources and processes `Vyavhar' in Ancient India meant legalism, dispute in Courts and legal process. - Reproduced.
Keywords: Legal theory - India; Legal theory